Optical Fiber Communication Conference (OFC) 2021 2021
DOI: 10.1364/ofc.2021.tu5c.5
|View full text |Cite
|
Sign up to set email alerts
|

High-Power, Low-Noise, and High-Speed 850 nm VCSEL Arrays with for Optical Wireless Transmission

Abstract: 850nm VCSEL arrays (7x7) using Zn-diffusion/Oxide-relief apertures have been demonstrated. It exhibits high CW power (190 mW), dampening E-O frequency response, and wide 3-dB E-O bandwidths (13 GHz). 25Gbit/sec error-free transmission has been demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…We adopt discrete multi-tone (DMT) modulation with adaptive bit-and-power-loading to maximise the achievable data rate of the OWC link. We have obtained 38 Gbps at a link distance of 2.5 m, which is about a 50% increase in the data rate compared to the work in [8] and [11]. Based on the analysis in [10], when spatial division multiplexing is considered, a 5×5 array based on such VCSELs can potentially achieve Tbps communications.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…We adopt discrete multi-tone (DMT) modulation with adaptive bit-and-power-loading to maximise the achievable data rate of the OWC link. We have obtained 38 Gbps at a link distance of 2.5 m, which is about a 50% increase in the data rate compared to the work in [8] and [11]. Based on the analysis in [10], when spatial division multiplexing is considered, a 5×5 array based on such VCSELs can potentially achieve Tbps communications.…”
Section: Introductionmentioning
confidence: 81%
“…For instance, the study in [7] practically demonstrated a data rate of 8.23 Gbps over a 1 m OWC channel with an optical power of ∼5 dBm. A higher data rate of 25 Gbps was achieved using a 7×7 VCSEL array with an optical power of ∼22 dBm [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation